Structural dependence of threshold displacement energies in rutile, anatase and brookite TiO2 - Robinson, M.; Marks, N.A.; Lumpkin, G.R. (Materials chemistry and physics, 2014)
Systematic molecular dynamics simulations of low energy cascades have been performed to examine how threshold displacement events are effected by changes in crystal structure. Exploiting the structural proximity of the rutile, anatase and brookite polymorphs of TiO2, a quantitative examination of defect production has been carried out including detailed defect analysis and the determination of values of the threshold displacement energy (Ed). Across all polymorphs comparable values of Ed are reported for oxygen at around 20 eV, with the value for Ti in rutile (73 ± 2 eV) significantly higher than that in brookite (34 ± 1 eV) and anatase (39 ± 1 eV). Quantifying defect formation probability as a function of Primary Knock-on Atom (PKA) energy, simulations in rutile indicate a consistent reduction in defect formation at energies higher than Ed relative to anatase and brookite. Defect cluster analysis reveals a significant proportion of di-Frenkel pairs in anatase at Ti PKA energies around Ed. These clusters, which are stabilised by the localisation of two Frenkel pairs, are associated with a recombination barrier of approximately 0.19 eV. As such, annihilation is likely under typical experimental conditions which suggests an expected increase in the measured Ti value of Ed. Identical O defect populations produced at the threshold by the O PKA in both rutile and anatase explain the comparable values of Ed. At higher O PKA energies, the commencement of defect production on both sublattices in anatase is observed in contrast to the confinement of defects to the O sublattice in rutile. The overall trends reported are consistent with in-situ irradiation experiments and thermal spike simulations, suggesting the contrasting radiation response of the polymorphs of TiO2 is apparent during the initial stages of defect production. •Systematic calculation of threshold displacement energies (Ed) in TiO2 polymorphs.•Ti Ed values of 73, 39 and 34 eV for rutile, anatase and brookite.•Comparable O values of Ed at around 20 eV.•Resilience to displacements and defect formation at higher energies in rutile.•Build up of transient, localized di-Frenkel pair defects in anatase.